'It's a constant changing environment, and we're just playing catch up': Hospital food services, food waste, and COVID‐19. Issue 2 (17th July 2022) - Cook, Nathan; Goodwin, Denise; Collins, Jorja; Porter, Judi
Abstract: Aims: Hospital food service operations have been affected by the COVID‐19 pandemic, particularly resulting in increased waste. The aim of this research was to explore the impact of the COVID‐19 pandemic on hospital food services, particularly on food waste and the completion of food waste audits. Methods: A qualitative interview research design was used. Semi‐structured interviews were completed and recorded via Zoom, focusing on the barriers and enablers towards the completion of hospital food waste audits. Twenty‐one participants were interviewed from 12 hospitals. No questions were related to the COVID‐19 pandemic and its impact on hospital food services, however this issue frequently emerged during interviews. Data were coded following inductive thematic analysis. Results: Five themes were generated from the interviews related to COVID‐19 and hospital food services; impacts on practice, labour, change, technology and post‐pandemic expectations. Participants reported COVID‐19 negatively affected food service operations. Changes included increased food waste, contact restrictions, and labour shortages. Nonetheless, hospitals embraced the challenge and created new positions, trialled different food waste data collection methods, and utilised technology to support food service operations around COVID‐19 restrictions. Conclusions: Despite the impact COVID‐19 had on hospital food services, including their ability to audit food waste and increased food waste generation, the response from food services has demonstrated their adaptability to change. Sustainable healthcare, including the aggregate measuring and reduction of food waste in hospital food services, is an essential transition post‐pandemic, and may be facilitated through the operational changes forced by COVID‐19.